2020
DOI: 10.33965/ijcsis_2020150107
|View full text |Cite
|
Sign up to set email alerts
|

Using the Unified Theory of Acceptance and Use of Technology (Utaut) Model to Determine Factors Affecting Mobile Learning Adoption in the Workplace: A Study of the Science Museum Group

Abstract: It has been observed that mobile learning (mLearning) in institutions like Museums in the United Kingdom (UK) has been underutilized. mLearning usage could potentially increase productivity by delivering just-in-time technical knowledge to the science museum group (SMG) staff. This study uses the unified theory of acceptance and use of technology (UTAUT) model to determine factors affecting mLearning adoption at the SMG. Two research questions were formulated based on an adaptation of the UTAUT model. 1) What … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…All study model constructs have an average level and explain that these constructs affect students' acceptance of e-learning technology and positive behavioral intention toward this system. This result consistent with the conceptual framework of the UTAUT model and with the study result of Evans & Roux (2015), Welch et al (2020), andAbubakar andAhmad (2015).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…All study model constructs have an average level and explain that these constructs affect students' acceptance of e-learning technology and positive behavioral intention toward this system. This result consistent with the conceptual framework of the UTAUT model and with the study result of Evans & Roux (2015), Welch et al (2020), andAbubakar andAhmad (2015).…”
supporting
confidence: 91%
“…To answer the study questions and understanding students` behavioral intentions for adopting e-learning technology, the unified theory of technology acceptance and use (UTAUT) presented by Venkatesh et al (2003) is the most comprehensive as it serves as a base-line model and has been applied to the study of a variety of technologies related to the acceptance and use of technology (Venkatish et al, 2012). The UTAUT model includes a combination of four constructs nominated from eight models of e-learning technology acceptance and behavioral intent to adopt it (TAM, TAM2, IDT, TPB, TRA, TM, SCT, and Combined TAM & TPB), these are Performance Expectancy (PE), Efforts Expectancy (EE), Social Influence (SI), and Facilitating Conditions (FC) (Welch et al, 2020). Based on the theoretical background of the unified theory of acceptance and use of technology (UTAUT) and the previous discussion, the researchers made some modifications to the model regarding the moderating factors shown in figure 1.…”
Section: Model Specification Of Studymentioning
confidence: 99%
“…According to the items for perceived ease of use proposed by Welch et al (2020), the subjects are requested to evaluate the perceived ease of use of digital technology.…”
Section: Behavior Intentionmentioning
confidence: 99%
“…Evidence from numerous cohort research has shown that the behavioural intention to use online learning exists in accordance with user understanding. Specifically, Performance Expectancy (PE), Effort Expectancy (EE), Facilitating Conditions (FC), Social Influence (SI) and Habit (HT) have significant relation with Behavioural Intention (BI) and Attitude Towards Use behaviour (ATU) (Bhimasta and Suprapto, 2016; Fagan, 2019; Welch et al , 2020; Yildiz et al , 2020). In the framework of online teaching and learning, both teachers and students may believe that online education system is helpful in enhancing their work performance and learning productivity (Al-Adwan et al , 2018), apart from allowing them to acquire knowledge conveniently and rapidly (Jackman, 2014).…”
Section: Introductionmentioning
confidence: 99%